2019
DOI: 10.1002/ijc.31930
|View full text |Cite|
|
Sign up to set email alerts
|

A BAP31 intrabody induces gastric cancer cell death by inhibiting p27kip1 proteasome degradation

Abstract: B‐cell receptor‐associated protein 31 (BAP31) is a ubiquitously expressed endoplasmic reticulum (ER) membrane protein that has been found to be overexpressed in gastric intestinal‐type adenocarcinoma. We first studied the relationship of BAP31 with 84 kinds of tumor‐associated antigens and found that BAP31 can specifically interact with and regulate the proteasome degradation of the cyclin kinase inhibitor p27kip1, which is one of the most frequently dysregulated tumor suppressor proteins in human cancers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Also, the formation of the Fis1-BAP31-tethering complex can be induced by exogenous inducers of apoptosis [43]. Consistent with the previous data, cell apoptosis-related to Fis1 overexpression is associated with the excessive ERmitochondria Ca 2+ transfer [130].…”
Section: Other Functions Of Mamssupporting
confidence: 85%
“…Also, the formation of the Fis1-BAP31-tethering complex can be induced by exogenous inducers of apoptosis [43]. Consistent with the previous data, cell apoptosis-related to Fis1 overexpression is associated with the excessive ERmitochondria Ca 2+ transfer [130].…”
Section: Other Functions Of Mamssupporting
confidence: 85%
“…The abnormal high expression of BAP31 was initially detected in cervical cancer, and BAP31 expression was positively correlated with the clinical stages of cervical cancer (Dang et al, 2018). Subsequently, Chen et al (2019) demonstrated that BAP31 can promote the proliferation of gastric cancer cells by interacting with cyclin kinase inhibitor p27 kip1 . Xu et al (2019) found that miR-451a binds to the 5 ′ -UTR of BAP31, induces the endoplasmic reticulum (ER) stress, and leads to the inhibition of cell proliferation in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the mechanism of Bap31 on MAOA, we firstly detected the regulation of Bap31 on the degradation of MAOA. Although Bap31 affects the degradation of many proteins (Wang et al, 2008;Chen et al, 2019), the regulation of Bap31 on MAOA expressions does not appear to be dependent on these effects. Bap31 did not directly affect the ubiqutin-mediated degradation of MAOA in MAOA-HA stable cells with knockdown or overexpression of Bap31 (Figures 3A,B).…”
Section: Discussionmentioning
confidence: 94%